Risk Factor for Erythropoietin Resistance in Hemodialysis Patient : Literature Review - Rachma Greta Perdana Putri; Amanatus Sholikhah; Novi Sukirto (Ahmad Dahlan Medical Journal, 2020)
Anaemia become the complication of chronic kidney disease (CKD) which was caused by decreasing of erythropoietin. Erythropoietin stimulating agent (ESA) therapy is one of therapy to overcome the problem, but until 34% of patients have lack of response to ESA treatment. Anaemia in CKD related to the worsen of the diseases, quality of life, and mortality of patients. Decreasing of the response to erythropoietin need to be evaluated to correct anaemic condition. This review is aim to explain the risk factor for erythropoietin resistance. The literature for this review was collected through PUBMED and google scholar. Erythropoietin is glycoprotein secreted 90% by interstitial cells of kidney and 10% by liver cells. The functions of erythropoietin are stimulate the proliferation and cells differentiation in bone marrow, and enhance erythropoiesis. Renal damage can inhibit the secretion of erythropoietin. In patients with ESA treatment, risk factors for resistance are iron deficiency, inadequate haemodialysis, inflammation, hyperparathyroid, nutrition disturbance, antibody mediated Pure Red Cell Aplastic (PRCA). The risk factor can be influenced by genetic variation. Conclusion of this review, there are several factor that influence the response of erythropoietin in hemodialisa patients. Hence, study related anaemia in CKD need further study to optimalize the treatment.